P-124 ASSOCIATED FACTORS WITH CLINICAL COURSE OF VASCULAR LIVER DISEASE IN A PUBLIC HOSPITAL IN PERU - CESAR CASTRO VILLALOBOS; Alexandra Linares Tang; Sheyla Ludeña Pacheco; Rosario Mayorga Márquez; Jorge Garavito Rentería; Rommel Zambrano Huilla (Annals of Hepatology)
Conflict of interest: No Introduction and Objectives: Vascular liver disease comprises a heterogeneous group of disorders (portal vein thrombosis, Budd-Chiari syndrome and porto-sinusoidal vascular disease (PSVD) as the main ones) that affect the liver vascular system, characterized by the development of elevated portal venous pressure in the absence of cirrhosis. The incidence varies worldwide, however, this disease occurs in less than 10% of the population. The aim of this study was to identify the associated factors with hospital admissions due to portal hypertension related-complication (PHrC) in a public hospital in Peru. Patients / Materials and Methods: We performed observational retrospective study. Demographic information, biochemical parameters, imaging techniques, liver stiffness measurements and liver biopsy were collected from medical records. Presence of a previous underlying liver disease was discarded by clinical, radiological, elastography, and when doubts liver biopsy. Results and Discussion: 35 patients (18 were men and 17 women with a median of age of 34 (25-40) years) were included. Portal vein thrombosis (PVT) was the most frequent etiology (60%) and gastrointestinal bleeding was the most common PHrC (71%). Fifteen patients had more than three hospital admissions. PVT [OR: 5.1 (95% CI: 1.2 - 24.5), p<0.05] and gastrointestinal bleeding [OR: 11.4 (95% CI: 1.7 - 228), p<0.05] were associated with more than three hospital admissions. Conclusions: In this first study of vascular liver disease in Peru, portal vein thrombosis was the most frequent etiology. Portal vein thrombosis and gastrointestinal bleeding due to portal hypertension related-complication develop more hospital admissions.